Immunological Role of the Maternal Uterine Microbiome in Pregnancy: Pregnancies Pathologies and Alterated Microbiota - Bardos, Jonah; Fiorentino, Desiree; Longman, Ryan E.; Paidas, Michael (Frontiers in Immunology, 2020)
Understanding what happens at the time of embryo implantation has been the subject of significant research. Investigators from many differing fields including maternal fetal medicine, microbiology, genetics, reproductive endocrinology and immunology have all been studying the moment the embryo interacts with the maternal endometrium. A perfect relationship between the uterus and the embryo, mediated by a tightly controlled interaction between the embryo and the endometrium, is required for successful implantation. Any factors affecting this communication, such as altered microbiome may lead to poor reproductive outcomes. Current theories suggest that altered microbiota may trigger an inflammatory response in the endometrium that affects the success of embryo implantation, as inflammatory mediators are tightly regulated during the adhesion of the blastocyst to the epithelial endometrial wall. In this review, we will highlight the various microbiome found during the periconceptual period, the microbiomes interaction with immunological responses surrounding the time of implantation, its effect on implantation, placentation and ultimately maternal and neonatal outcomes.